Annotated Translation of The 'Slow Violence' of Malnutrition in South Africa - Rini Adriati (ESENSI LINGUA, 2022)
This journal article is based on an annotated translation research. The object of the research is a text with a title of the ‘Slow Violence’ of Malnutrition in South Africa published by Unicef South Africa. The purpose of this research are: 1) To identify the problems encountered by the researchers during the translation process. 2) To offer the solution to solve the problems during the translation process. This study employed a descriptive qualitative research methodology. The result of the research consists of two main point. First, the findings reveals that from fifteen difficult problems, both in word and phrase levels, the author focused and selected nine items for annotations. Second, those problems were solved by several translation theories from Newmark and Vinay and Darbelnet.